Exploring Dynamic Program Behavior with Frames and Phases - César, Divino; Araújo, Guido; Borin, Edson (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
The kind and amount of hardware resources demanded for the efficient execution of different programs are not the same. In fact, even the same program may have different requirements at different moments during its execution. However, current computers hardware is not designed to adapt itself during the execution of programs. The continuous need for energy efficient computation and the ever-decreasing size of transistors will enable the design and manufacturing of smart processors capable of adapting itself to meet the needs of the executing software. In this work, we investigate how program phase analysis and dynamic code optimization can be combined to achieve these goals. We first propose and evaluate a technique to perform online program phase detection based on the execution of frames built by the replay framework and then we show how the phases information can be used to improve the effectiveness of the replay framework.